PENGARUH EMOJI DALAM MEDIA LAYANAN BIMBINGAN DAN KONSELING ONLINE TERHADAP METAKOGNITIF KONSELI - Suci Nora Julina Putri; Ummu Aiman; M Yunus Sudirman; Nanda Alfan Kurniawan; Parid Rilo Pambudi (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2021)
Online guidance and counseling services began to thrive during the Covid-19 pandemic in the 21st century. The emergence of online-based media and platforms offers various facilities that can support guidance and counseling services more effectively, efficiently, and professionally. Electronic devices that can be used are computers, smartphones, tape recorders, and several technology devices. Technological sophistication attracts participation in various life activities, including education-oriented communication processes. Guidance and counseling are part of educational activities. A collaboration of technological sophistication with guidance and counseling can be supported through attractive features in a device. Emojis are one of the features available on some technology devices. Generally, emojis are used in the communication process to represent feelings and thoughts when conveying messages without the need to write a complete statement. This writing aims to provide information about emojis in online guidance and counseling service media. The writing method used is a literature study, data sources obtained from research articles and books relevant to writing. The data source analysis results show that emojis have a significant effect on the application of online guidance and counseling services for counselees in schools.